Validation of the Adolescent Gambling Expectancies Survey (AGES) among Korean college students: A pilot study. - Lee, Sungkyu; Na, Jihun; Sung, Hyeyeon (Journal of Human Behavior in the Social Environment)
Objective: Although several studies have found the Adolescent Gambling Expectancies Survey (AGES) valid and reliable for high school students and college students, the applicability of the AGES to Korean college students remains unknown. The objective of this study was to examine the validity of the Adolescent Gambling Expectancies Survey (AGES) developed by Wickwire et al. (2010). Methods: The study sample consisted of 481 college students in Korea, and the data were collected through an online survey. To examine the construct validity and internal consistency of the Korean version of the AGES (K-AGES), an item analysis and a confirmatory factor analysis were conducted. Results: The results of item analysis have identified 22 items with five factors: Material gain, negative affect, positive self-evaluation, negative social consequences, and parent disapproval. In addition, the results of confirmatory factor analysis show these 22 items fit the data well. Conclusions: The K- AGES has strong psychometrics, including good construct validity and reliability, and, hence, it may be a useful tool for assessing, preventing, and treating gambling problems in college students.